The impact of antiepileptic drug therapy on oral health in children with epilepsy: current evidence, mechanisms, and management strategies - Sołowiej, Elżbieta; Sołowiej, Weronika; Blecharz-Klin, Kamilla (Prospects in Pharmaceutical Sciences, 2025)
Epilepsy represents one of the most common chronic neurological disorders worldwide, with approximately half of all cases diagnosed during childhood or adolescence. Although the condition remains incurable, effective seizure control can be achieved in up to 70% of patients through appropriately selected antiepileptic drugs (AEDs), administered as monotherapy or in combination. Despite their therapeutic efficacy, AEDs are associated with a range of adverse effects, including those affecting oral health, which may substantially impair patients’ quality of life. This review summarizes current evidence regarding the impact of AED therapy on oral health in children with epilepsy and discusses potential pathophysiological mechanisms underlying these adverse effects. A comprehensive literature search was performed in the PubMed and Google Scholar databases using the free-text terms and Medical Subject Headings (MeSH), such as “Epilepsy/drug therapy” and “Anticonvulsants/adverse effects” and the following keywords: “antiepileptic drugs & side effects,” “antiepileptic drugs & oral health status in children,” “oral side effects,” “antiepileptic drugs,” as well as relevant synonyms such as “antiseizure medications,” “AEDs,” and “anticonvulsants.” The review includes data from systematic reviews, meta-analyses, and original research conducted in Europe and globally. Reported oral manifestations associated with AED use include gingival overgrowth, gingivitis, xerostomia, and glossitis, particularly linked to first-generation agents such as phenytoin and valproic acid. Pediatric patients undergoing long-term AED therapy demonstrate increased susceptibility to dental caries, periodontal disease, tooth loss, and maxillofacial bone demineralization, which may elevate the risk of fractures following trauma. Further studies are warranted to elucidate the oral health implications of newer-generation AEDs and to clarify the molecular mechanisms responsible for these complications. Given the chronic nature of epilepsy and the cumulative impact of long-term pharmacotherapy, children receiving AEDs require individualized preventive strategies, emphasizing meticulous oral hygiene and regular dental monitoring to reduce the risk of treatment-related oral pathology.